Association of a blood-based aging biomarker index with death and chronic disease: Cardiovascular Health Study. - Zhang, Xiao; Sanders, Jason L; Boudreau, Robert M; Arnold, Alice M; Justice, Jamie N; Espeland, Mark A; Kuchel, George A; Barzilai, Nir; Kuller, Lewis H; Lopez, Oscar L; Kritchevsky, Stephen B; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2023)
BACKGROUND: A goal of gerontology is to discover phenotypes that reflect biological aging distinct from disease pathogenesis. Biomarkers that are strongly associated with mortality could be used to define such a phenotype. However, the relation of such an index with multiple chronic conditions warrants further exploration. METHODS: A Biomarker Index (BI) was constructed in the Cardiovascular Health Study (N=3197), with a mean age of 74 years. The BI incorporated circulating levels of new biomarkers, including insulin-like growth factor-1, interleukin-6, amino-terminal pro-B-type natriuretic peptide, cystatin-C, C-reactive protein, tumor necrosis factor-alpha soluble receptor 1, fasting insulin, and fasting glucose, and was built based on their relationships with mortality. Cox proportional hazards models predicting a composite of death and chronic disease involving cardiovascular disease, dementia, and cancer were calculated with 6 years of follow-up. RESULTS: The hazard ratio (HR, 95% CI) for the composite outcome of death or chronic disease per category of BI was 1.65 (1.52, 1.80) and 1.75 (1.58, 1.94) in women and men, respectively. The HR (95% CI) per 5 years of age was 1.57 (1.48, 1.67) and 1.55 (1.44, 1.67) in women and men, respectively. Moreover, BI could attenuate the effect of age on the composite outcome by 16.7% and 22.0% in women and men, respectively. CONCLUSIONS: BI was significantly and independently associated with a composite outcome of death and chronic disease, and attenuated the effect of age. The BI that is composed of plasma biomarkers may be a practical intermediate phenotype for interventions aiming to modify the course of aging.